UJI CO-FIRING BATUBARA DENGAN BRIKET MSW MENGGUNAKAN INSINERATOR FLUIDIZED BED - Immanuel, Bryan Steve; Winaya, I Nyoman Suprapta; Suryawan, I Gede Putu Agus; Pratama, I Putu Angga Yuda (Teknik Desain Mekanika; Vol 13 No 3 (2024): Juli 2024 : Teknik Desain Mekanika, 2024)
Abstract The co-firing method has emerged as a promising strategy in reducing dependence on fossil fuels in the power generation industry. Co-firing involves co-burning biomass fuel with conventional fossil fuel in an existing combustion furnace Utilizing energy from municipal solid waste (MSW) is a feasible method through various processes, one of which is combustion. This research aims to investigate the combustion performance of co-firing in a fluidized bed incinerator using MSW briquette fuel sourced from the TPST Kertalangu in Denpasar, combined with coal fuel. The study utilizes a temperature of 800°C supplied by a heater that controlled through a control panel. The experiment on burning MSW briquettes and coal was conducted in a fluidized bed incinerator with a combustion chamber volume of 902.75 cm3, a fluidization chamber of 451.375 cm3, a fuel chamber of 150.46 cm3, and a bed material chamber of 300.92 cm3. Through the mass fraction conversion process, it was determined that the fuel mass requirement was 140 grams to fill the fuel volume inside the reactor. Thus, the 6% briquette percentage resulted in a mass ratio of 11.2 grams MSW briquettes and 128.8 grams coal, following the predetermined percentage of MSW briquettes in this study. The research utilized an air velocity of 9m/s to maintain combustion quality. The results of this experimental study indicate a decrease in combustion efficiency with an increase in the amount of MSW briquettes. The best performance occurred at the 8% briquette variation, producing an NPHR value of 881.7 kcal/kWh. Keywords: Co-firing, MSW briquette, fluidized bed, incinerator, NPHR